Oral health self‐care behaviours in serious mental illness: A systematic review and meta‐analysis. (3rd May 2021) - Turner, Elizabeth; Berry, Katherine; Aggarwal, Vishal R.; Quinlivan, Leah; Villanueva, Timothy; Palmier‐Claus, Jasper
Abstract: Aim: To understand the relationship between serious mental illness and oral health self‐care behaviours using meta‐analytic methods and a narrative synthesis of available literature. Method: The review followed the Preferred Reporting Items for Systematic Reviews and Meta‐analyses guidelines [PROSPERO reference: CRD42020176779]. Search terms pertaining to serious mental illness and oral health were entered into EMBASE, PsycINFO, Medline and CINAHL. Eligible studies included a sample of people with a serious mental illness and a quantitative measure of an oral health self‐care behaviour (eg dental visits, toothbrushing). The Effective Public Health Practice Project tool was utilised to appraise the quality of the literature. Studies in the meta‐analysis contained a non‐clinical or general population comparator sample. Results: People with a serious mental illness were significantly less likely to visit the dentist (OR 0.46, 95% CI 0.32–0.065, p > 0.001) or brush their teeth (OR 0.19, 95% CI 0.08–0.42, p < 0.001) when compared to non‐clinical comparator samples. Few studies explored other oral health self‐care behaviours (eg flossing and mouth washing), but uptake was generally low in people with a serious mental illness. The study quality of included studies was variable. Conclusions: The research showed a reduced uptake of oral health self‐care behaviours in people with a serious mental illness. Suboptimal oral health can negatively impact on physical, social and psychological functioning. Further research is needed to understand the reasons for low rates of oral health self‐care behaviours in this population.